A microsimulation approach to an optimal Swedish income tax - Peter Ericson; Lennart Flood (Institute for the Study of Labor (IZA), 2009)
This paper follows the theory of optimal taxation and the goal is to identify a tax/benefit design that maximizes social welfare. A two stage process is proposed where the individuals preferred choice of leisure and consumption is solved in the first stage, and the second stage identifies the tax/benefit system that maximize the social welfare function. Our study deviates from the mainstream literature as the first stage is based on a static micro simulation model with behavioral responses. The behavioral responses take two different forms and use two different types of models; first binary models that describe mobility in/out from non-work states such as old age pension, disability, unemployment, long term sickness, and second models that describe change in working hours and welfare participation. Compared to the current Swedish income tax, our results suggest that increased basic deduction and in-work tax credit in combination with a reduction of the progressive national taxes would increase welfare. We also find strong support for increased housing allowances. The reforms are financed by a tax based on the same tax base as the proportional municipal income tax.
Keywords: C8; D31; H24; 330; Micro simulation; tax-benefit system; in-work tax credit reform; optimal taxation; Einkommensteuer; Optimale Besteuerung; Sozialtransfer; Steuerbegünstigung; Soziale Wohlfahrtsfunktion; Schweden